2019
DOI: 10.1038/s12276-019-0259-6
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of long noncoding RNA PVT1 inhibits podocyte damage and apoptosis in diabetic nephropathy by upregulating FOXA1

Abstract: The number of patients with diabetic nephropathy (DN) is still on the rise worldwide, and this requires the development of new therapeutic strategies. Recent reports have highlighted genetic factors in the treatment of DN. Herein, we aimed to study the roles of long noncoding RNA (lncRNA) plasmacytoma variant translocation 1 (PVT1) and histone 3 lysine 27 trimethylation (H3K27me3) in DN. A model of DN was established by inducing diabetes in mice with streptozotocin. Mouse podocyte clone 5 (MPC5) podocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 27 publications
4
56
1
Order By: Relevance
“…Interestingly, our findings demonstrated that lncRNA NEAT1 modulated LATS2 expression through increased recruitment of EZH2 to the LATS2 promoter and promoted the methylation of H3K27 to H3K27me3. Likewise, it has also been indicated that lncRNA plasmacytoma variant translocation 1 can recruit EZH2 to elevate the accumulation of H3K27me3 41 , which further validates our results.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, our findings demonstrated that lncRNA NEAT1 modulated LATS2 expression through increased recruitment of EZH2 to the LATS2 promoter and promoted the methylation of H3K27 to H3K27me3. Likewise, it has also been indicated that lncRNA plasmacytoma variant translocation 1 can recruit EZH2 to elevate the accumulation of H3K27me3 41 , which further validates our results.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, PVT1, a well-studied lncRNA, was highly expressed in primary podocytes in DN patients. The silencing of lncRNA PVT1 exerted inhibitory effects on podocyte damage and apoptosis via upregulating FOXA1 [80]. More importantly, lncRNA SOX2OT was confirmed to mitigate podocyte injury induced by the high glucose through autophagy induction by the miR-9/SIRT1 axis.…”
Section: Lncrnas In Dnmentioning
confidence: 84%
“…Upregulated β -arrestin 1/2 promoted podocyte apoptosis and the p53 pathway by increasing Bax, cleaved-caspase-3, and p-p53 levels in HG-induced podocytes [ 125 ]. High expression of PVT1 or low expression of FOXA1 can downregulate the expression of synaptophysin and podocyte protein, decrease the expression of Bcl-2, and increase the expression of Bax and cleaved-caspase-3, thus promoting podocyte apoptosis [ 126 ]. Chen et al [ 127 ] found that Sam68 was upregulated in a time- and dose-dependent manner in in vitro HG-treated podocytes.…”
Section: Morphological Changes Of Podocytesmentioning
confidence: 99%